Fresh start - Galligan, Gale (New York : Graphix, an imprint of Scholastic, 2025)
Ollie Herisson's dad is a diplomat, which means her family moves around a lot. She has already lived in Singapore, Korea, France, and the United States. When Ollie starts at a new school, she doesn't worry about making a good impression because she knows that when her family inevitably moves again, she'll get a fresh start somewhere else. A complete reset. It doesn't matter if her classmates think she's weird for pretending that she lives in the world of an imagined anime, or if she makes an enemy out of the most popular girl in her class, or if she does something hugely embarrassing! But after moving from Germany to Virginia and having a mortifying first day at her new school, Ollie is shocked to learn that her parents are going to buy a house so that Ollie and her sister, Cat, can finish grade school in one place. Can Ollie figure out how to both be herself and make real friends when she can't run away from her life?
New school. New friends. New challenges--Front cover.
School Library Journal starred, December 2024
Publishers Weekly, October 2024
Kirkus Starred, November 2024
3-6
GN420L
Keywords: Friendship -- Comic books, strips, etc; Friendship -- Juvenile fiction; Bullying -- Comic books, strips, etc; Bullying -- Juvenile fiction; Middle schools -- Comic books, strips, etc; Middle schools -- Juvenile fiction; Thai Americans -- Comic books, strips, etc; Thai Americans -- Juvenile fiction; Friendship -- Fiction; Bullying -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Thai Americans -- Fiction; School comics; Graphic novels; LGBTQ+ fiction; Comics (Graphic works)